A polysaccharide gel made of gellan gum improves oocyte maturation and embryonic development in pigs - Shunsuke HARA; Koumei SHIRASUNA; Hisataka IWATA (The Society for Reproduction and Development, 2024)
Gellan gum (GG) is a soft, tractable, and natural polysaccharide substrate used for cell incubation. In this study, we examined the effects of GG on porcine oocyte maturation. Cumulus cells and oocyte complexes (COCs) were collected from slaughterhouse-derived porcine ovaries and cultured on plastic plates containing 0.05% or 0.1% GG gels. The 0.1% GG gel improved the maturation rate and quality of blastocysts, as determined by the total cell number and the rate of abnormally condensed nuclei. GG gels have antioxidant abilities and oocytes cultured on GG gels (0.05% and 0.1%) have reduced reactive oxygen species (ROS) content. Furthermore, GG gels (0.05% and 0.1%) increased F-actin formation, whereas treatment of oocytes with H2O2 reduced F-actin levels. GG gels increased the ATP content in oocytes but did not affect the mitochondrial DNA copy number or mitochondrial membrane potential. In addition, the medium cultured on 0.05% GG increased the glucose consumption of COCs. In conclusion, GG gel reduced ROS content, increased energy content, and improved subsequent embryonic development in pigs.